PENGARUH INTELLECTUAL CAPITAL, LEVERAGE, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN - Azlin Shakila Putri; Desrir Miftah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2021)
The objective of this study is to analyze the influence of intellectual capital, leverage, profitability and liquidity on firm value. Firm value is measured by price to book value (PBV), leverage is measured by debt to equity ratio (DER), profitability by return on equity (ROE) and liquidity by current ratio (CR). This research method is a quantitative research with sampling using a purpose sampling technique based on predetermined characteristics as many as 9 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2016 - 2019. The type of data used is secondary data and the analytical method used is panel data regression using Eviews. The results show that intellectual capital, leverage, profitability have a significant effect on firm value. However, liquidity has no effect on firm value.